PERTUMBUHAN BIBIT SAMBUNG PUCUK DINI KAKAO (Theobroma cacao L.) KLON SUL-1 DAN SUL-2 YANG DIBERI PUPUK ORGANIK CAIR BERBEDA KONSENTRASI - Iskandar M. Lapanjang, Usman Made, Putu Sribawanti (AGROTEKBIS, 2016)
The research aimed to obtain the better concentration of liquid organic fertilizer on the growth of each cacao, compare the growth of cleft grafting seedling of Sul 1 and Sul 2 cacao clones and gain the concentration of liquid organic fertilizer which was better on the growth of early grafting cacao seedling. The research was conducted in December 2015 to February 2016 in Green House of Faculty of Agriculture, Tadulako University. The research used two-factor Randomized Block Design. The first factor was clone consisting of Sul 1 and Sul 2 clones. The second factor was the concentration of liquid organic fertilizer consisting of concentration of liquid organic fertilizer by 0.0%, concentration of liquid organic fertilizer by 0.25%, concentration of liquid organic fertilizer by 0.50%, and concentration of liquid organic fertilizer by 0.75%. The data were analyzed by using analysis of variance of median value test done with BNJ 5%. The research showed that the concentration of liquid organic fertilizer by 0.75% is better on Sul 1 clone. It was shown by more numerous and long shoots, more numerous and wide leaves and the more total chlorophyll. Mean while, the concentration of liquid organic fertilizer which is better for Sul 2 clone is the 0.50%.       it was shown by more numerous and long shoots, more numerous and wide leaves and the more total chlorophyll.